Extensive Reannotation of the Genome of the Model Streptomycete Streptomyces lividans TK24 Based on Transcriptome and Proteome Information - Droste, Julian; Rückert, Christian; Kalinowski, Jörn; Hamed, Mohamed Belal; Anné, Jozef; Simoens, Kenneth; Bernaerts, Kristel; Economou, Anastassios; Busche, Tobias (Frontiers in Microbiology, 2021)
Streptomyces lividans TK24 is a relevant Gram-positive soil inhabiting bacterium and one of the model organisms of the genus Streptomyces. It is known for its potential to produce secondary metabolites, antibiotics and other industrially relevant products. S. lividans TK24 is the plasmid-free derivative of S. lividans 66 and a close genetic relative of the strain Streptomyces coelicolor A3(2). In this study, we used RNA-seq to improve the initial annotation of the S. lividans TK24 genome. In this context, 335 translation start sites (TLS) were corrected, 80 protein-coding sequences (CDS) were removed due to missing or misleading transcript evidence and, 2,550 CDS could be validated including 769 coding for uncharacterized proteins. Furthermore, we annotated 116 novel CDS, 14 small RNAs (sRNAs) and 2 novel tRNAs. The RNA-seq data of primary 5′-ends of transcripts were used to determine transcription start sites (TSS) in the genome. We identified 5,580 TSS, of which 4,812 were assigned to CDS and 768 to novel or antisense transcripts. Using the TSS data, promoter regions and their motifs were analyzed in detail, revealing a conserved -10 (TAnnnT) and a weakly conserved -35 region (nTGACn). Moreover, the 5´ untranslated region (UTRs) of S. lividans TK24 genes were analyzed regarding their lengthand revealed 21% leaderless transcripts. Several cis-regulatory elements, like riboswitches, or attenuator structures could be detected in the 5´-UTRs. The S. lividans TK24 transcriptome comprised 929 operons containing 2,274 genes. The genome harbors 29 secondary metabolite gene clusters of which 28 could be shown to be transcribed under at least one of the applied conditions. Comparison of the reannotated genome with that of the strain S. coelicolor A3(2) revealed high similarity. This study presents an extensive reannotation of the genome of the model organism S. lividans TK24 based on transcriptome and proteome analyses. The analysis of TSS data revealed insights into the promoter structure, 5´-UTRs, cis-regulatory elements, attenuator structures and novel transcripts, like small RNAs. Finally, the repertoire of secondary metabolite gene clusters was examined. These data provide a basis for future studies regarding gene characterization, transcriptional regulatory networks, and usage as a secondary metabolite producing strain.